Rehabilitation with dental implant in an atrophic region of the mandible using the Split Crest technique: case report (Research, Society and Development, 2021)
Introduction: The loss of alveolar volume is a clinical implication resulting from dental extractions, which bring potentially important compromises in the aesthetic and functional results of implant-supported rehabilitations. Surgical treatment is indicated in cases of patients with the presence of an important anatomical accident as to the quantity and quality of the remaining bone that is involved in thickness. Objective: The aim of this paper is to report a clinical case of rehabilitation with a dental implant using the Split crest technique. Case Report: A 37 year-old female patient presented as main complaint the absence of dental element 35.  After anamnesis, clinical examination and tomographic evaluation of the region of interest it was observed the remaining bone tissue with presence of important anatomical accident regarding the buccal volume. After presentation of treatment alternatives, we opted for bone crest expansion using the Split crest technique and immediate implant installation. The Split crest technique in the mandible is a predictable technique for expanding atrophic ridges. The technique proved to be feasible, providing a significant increase in ridge thickness, absence of complications and reduced treatment time for the patient. Final considerations: Allowing implant installation together with ridge expansion is the major advantage of using the technique to correct potentially important clinical implications in the aesthetic and functional outcome of implant-supported rehabilitations.